Postconflict development - Junne, Gerd (ed.); Verkoren, Willemijn (ed.) (New Delhi, 2006)
The authors focus on the need to move beyond emergency relief to create new social and economic structures that can serve as the foundations for a lasting peace. Prosperity, they acknowledge, does not guarantee peace; but a lack of economic development will almost certainly lead to renewed violence. This conviction informs their thorough discussion of the policy dilemmas confronted in postconflict situations and a range of concrete, successful approaches to resolve them.
Keywords: Economic development